2021
DOI: 10.3906/sag-2005-225
|View full text |Cite
|
Sign up to set email alerts
|

Sural nerve harvest for infants: integrated with information based on anatomical dissections

Abstract: Background/aim: The aim of the present study was to determine the course and possible variations of the sural nerve with all anatomical details in human fetal cadavers. Materials and methods: This study was performed on 60 fetal cadavers. Formation type and level of the sural nerve was detected. Results: According to trimesters, it was determined that the mean transverse and vertical distance between the lowest point of the LM and the SN varied between 1.1-2.9 mm and 1.54-3.58 mm, respectively. Type 2 was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…We found Type 4 in most of the lower limbs evaluated. Previous studies performed on fetuses corroborate this, as exempli ed by Büyükmumcu et al and Ulcay et al [4,29], which show a high prevalence of this anatomical pattern. Studies in adults have rati ed this information and set Type 4 as the classic pattern [1,5,6,14,17,23,31].…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…We found Type 4 in most of the lower limbs evaluated. Previous studies performed on fetuses corroborate this, as exempli ed by Büyükmumcu et al and Ulcay et al [4,29], which show a high prevalence of this anatomical pattern. Studies in adults have rati ed this information and set Type 4 as the classic pattern [1,5,6,14,17,23,31].…”
Section: Discussionsupporting
confidence: 64%
“…Type 6 was reported in all previous articles in both fetal and adult populations. This pattern was found in seven studies with Asian samples [10,12,14,17,24,26,31] and ve studies with Eurasian ethnicity, all from Turkey [1,2,4,7,29]. However, only three European studies showed Type 6 [15,21,28].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations